Interannual variation in evapotranspiration in an urban forest reserve with respect to drought - Yang, Ruizhi; Liu, Peng; Tian, Yun; Ma, Jingyong; Bai, Yujie; Li, Cheng; Huang, Songyu; Mu, Yanmei; Hayat, Muhammad; Iqbal, Sundas; Yu, Haiqun; Zhang, Feng; et al. (Frontiers in Forests and Global Change, 2023)
Introduction A warming global climate is expected to perturb the hydrological cycle, resulting in deviations in both frequency and duration of drought and thus being hypothesized to lead to interannual variation in evapotranspiration (ET). Interannual variation in ET in urban forest ecosystems in response to drought remains poorly understood. Methods Here, ET in an urban forest reserve in the megalopolis of Beijing was investigated using eddy-covariance measurements collected over six consecutive years (2012–2017). Results The mean annual cumulative ET was 462 ± 83mm (±first standard deviation), with a coefficient of variation of 18%. Interannual variation in both annual and monthly ET was shown to be largely controlled by canopy conductance (gs), affected by environmental factors. The main factors affecting interannual variation in monthly ET varied seasonally, namely, soil volumetric water content (VWC) and normalized difference vegetation index (NDVI) in spring, precipitation and soil temperature in summer, and VWC and net radiation (Rn) in autumn. Interannual variation in annual ET was driven largely by spring and mid-summer droughts induced by insufficient precipitation during the non-growing and mid-growing seasons, respectively. Spring drought reduced annual ET by restricting leafing out, shortening growing season length (GSL), and reducing the normalized difference vegetation index (NDVI). The summer drought reduced annual ET by reducing stomatal conductance. Discussion and conclusion Results from this study point to the importance of precipitation timing and volume and the soil moisture carry-over effect in controlling interannual variation in ecosystem ET. Irrigation during the early spring and mid-summer is viewed as a practical management measure for sustaining growth and better ecosystem services in urban forests in Northern China.